The Effects of Stress on Academic Performance of Senior High School Students in Ghana - Bekoe, Regina; Somuah, Stella; Akpalu, Vivian Louise; Ayisi, Loretta Akua (Advances in Social Sciences Research Journal, 2015)
This is a descriptive study carried out to assess the effect of Stress on academic performance among Senior High School (SHS) students in Ghana - a case of New Juaben municipality. The main objective of the study was to verify the effect of Stress on academic performance among Senior High Students in the municipality. The study population comprises the entire New Juaben SHS students’ population.  Primary   and secondary sources of data were employed for this study. Stratified sampling technique was used to collect data from respondents. The sample size for the study was three hundred and fifty (350) that is, twenty-five (25) first year SHS students and twenty-five (25) final year students from Seven SHS schools in the municipality. The findings show that stress is associated with poor academic performance. 85% of the respondents indicated that Stress affects academic performance. Also, the sources of stress among SHS Students includes boyfriend and girlfriend relationship problems, social activities, course load, examination, lack/ inadequate family support and feeling homesick. Most of the students in this study were found using combination of coping strategies. This is similar to different studies which show students utilize a number of strategies to cope with stress. The study recommends that guidance and counseling services should be a part of the school’s curricular.